Association of Night Sleep Duration and Ideal Cardiovascular Health in Rural China: The Henan Rural Cohort Study - Wu, Xueyan; Liu, Xiaotian; Liao, Wei; Kang, Ning; Sang, Shengxiang; Abdulai, Tanko; Zhai, Zhihan; Wang, Chongjian; Wang, Xiaoqiong; Li, Yuqian (Frontiers in Public Health, 2021)
Introduction: We aimed to explore the association between night sleep duration and ideal cardiovascular health (ICH) among Chinese rural population. Methods: In all, 35,094 participants were included from the Henan Rural Cohort study. Information on sleep was collected using the Pittsburgh Sleep Quality Index. The ICH scores were evaluated. The associations between night sleep duration and ICH were examined using both linear regression and logistic regression models. Results: The mean night sleep duration for all participants was 7.75 ± 1.28 h. Compared with those with night sleep duration of 7 to <9 h by using linear regression model, a significant decrease in ICH scores was observed for participants with shorter [−0.077 (−0.131, −0.024)] and longer [−0.079 (−0.121, −0.036)] night sleep duration. Compared with 7 to <9 h, longer sleep duration [0.919 (0.851, 0.992)] were associated with decreased odds of ideal CVH. Conclusions: Shorter and longer night sleep duration are negatively associated with ICH among rural population. This suggests that it may be beneficial to include night sleep duration assessment in cardiovascular risk screening.